2004
DOI: 10.1002/app.21215
|View full text |Cite
|
Sign up to set email alerts
|

Stress–strain behavior of blends of bacterial polyhydroxybutyrate

Abstract: A series of blends of bacterial poly(R-hydroxybutyrate) (PHB), with different miscible amorphous components, were prepared. The molecular mass of the amorphous components was varied from M n Ϸ 600 to 200,000 g/mol. Several factors were found to influence the stress-strain behavior of PHB blends: the glass-transition temperature, the average molecular mass of amorphous phase, the content of PHB in the blend, the crystallinity, and the drawing temperature. It was found that a high extension ratio at rupture R Ͼ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 43 publications
1
10
0
4
Order By: Relevance
“…The tensile test results showed that PHBV exhibited a typical brittle fracture with less than 10% strain values (around 5%). This happens for polymers that are tested above their glass transition temperature with quasi‐viscous flow behavior 13. The brittleness of these bacterial based polyesters arises from secondary crystallization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tensile test results showed that PHBV exhibited a typical brittle fracture with less than 10% strain values (around 5%). This happens for polymers that are tested above their glass transition temperature with quasi‐viscous flow behavior 13. The brittleness of these bacterial based polyesters arises from secondary crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…The brittleness of these bacterial based polyesters arises from secondary crystallization. This secondary crystallization affects the mobility of the amorphous phase creating brittle polymers 13. El‐Taweel et al13 further relates the brittleness of the polyhydroxybutyrate (PHB) with the % crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…PHB films are known to have fragile behavior with a deformation at break below 5 % and an elastic modulus around 1.5 GPa [29,30]. The brittleness of PHB was attributed to polymer glass transition that occurs ~ 0 ºC, leading to cold recrystallization at room temperature, which restricts the mobility of the amorphous phase in interfibrillar and/or interlamellar regions, and results in a failure at relatively low strains [31].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The elucidation of such properties is, therefore, fundamentally important to understand the mode of actions of these polyesters in the living organisms and the functionality in their applications. Extensive researches have been carried out on PHB and some of its copolymers using a variety of techniques including DSC [12,13], X-ray diffraction (XRD) [14,15] and NMR [16e19]. Among many physical techniques, highresolution solid-state NMR is not only non-invasive and nondestructive method to facilitate in situ investigations but also able to provide information on molecular structure, dynamics and interactions of polymers, especially natural polymers [20e22].…”
Section: Introductionmentioning
confidence: 99%